Expert System for Identification of Diseases of Toddlers using Bayes' Theorem Method - Sandi Manalu (International Journal of Basic and Applied Science, 2020)
The disease is very susceptible to occur in children under five because the immune system in children under five has not been fully developed. Lack of knowledge about toddlers' illnesses as well as the symptoms experienced frighten parents. Information needs that are very fast from an expert to deal with problems or diseases of children under five expected by parents or the community. So that is what drives the development of a software application, namely the expert system for identification of children under five. An expert system for identification of toddlers is made as a tool to diagnose diseases experienced by children under five by using the symptoms experienced by children under five as a tool to detect diseases experienced by children under five. The system can identify 5 types of diseases with 23 symptoms of the disease. This expert system uses methods for developing problem identification, system design, implementation, and testing. Inference in this expert system uses the Bayes theorem method. This system is built with Visual Basic and Microsoft access as the database. The results of the consultation with this system indicate that the system is able to determine the disease and treatment solutions and the initial treatment that must be done, based on the symptoms previously chosen by the user.